PENERAPAN TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS SISWA: SMA NEGERI 1 SINGOSARI MALANG - NANI TRIANA (Mitra Pendidikan, 2021)
In accordance with the formulation of the problem, this study aims to 1). Knowing the application of the Talking Stick learning model in learning English at SMA Negeri 1 Singosari Malang 2). Improving student learning activities which include visual activities, listening activities, oral activities, emotional activities, and writing activities after using the talking stick learning model in English learning at SMA Negeri 1 Singosari Malang 3. Improving English learning outcomes after using the talking stick learning model at SMA Negeri 1 Singosari Malang.This research includes classroom action research (Classroom Action Research) and is included in the scope of applied research (Applied Research) which combines knowledge, research, and action. This classroom action research was carried out in the odd semester of the 2019/2020 school year for 3 months, from September 2019 to November 2018 at SMA Negeri 1 Singosari Malang, which is located at Jalan. Ki Hajar Dewantoro No. 1 Banjararum Singosari. The subjects in this study were students of class XI IPA.B SMA Negeri 1 Singosari Malang, totaling 36 students. Based on the results of research and discussion, it can be concluded that the achievement of student learning outcomes in English subjects in Class XI IPA.B SMA Negeri 1 Singosari Malang can be improved through the Talking Stick learning model.